Probiotics: functional food ingredients with the potential to reduce hypertension - Chen, Zouquan; Liang, Wanjie; Liang, Jie; Dou, Jiaxin; Guo, Fangyu; Zhang, Daolei; Xu, Zhenshang; Wang, Ting (Frontiers in Cellular and Infection Microbiology, 2023)
Hypertension is an increasingly pressing public health concern across the globe. It can be triggered by a variety of factors such as age and diet, as well as the stress of modern life. The traditional treatment of hypertension includes calcium ion blockers, angiotensin Ⅱ receptor inhibitors and β-receptor blockers, but these drugs have at least some side effects. Recent studies have revealed that intestinal flora plays a vital role in maintaining and promoting human health. This is due to the type and amount of probiotics present in the flora. Probiotics can reduce hypertension symptoms through four mechanisms: regulating vascular oxidative stress, producing short-chain fatty acids, restoring endothelial cell function, and reducing inflammation. It has been reported that certain functional foods, using probiotics as their raw material, can modify the composition of intestinal flora, thus regulating hypertension symptoms. Consequently, utilizing the probiotic function of probiotics in conjunction with the properties of functional foods to treat hypertension is a novel, side-effect-free treatment method. This study seeks to summarize the various factors that contribute to hypertension, the mechanism of probiotics in mitigating hypertension, and the fermented functional foods with probiotic strains, in order to provide a basis for the development of functional foods which utilize probiotics as their raw material and may have the potential to reduce hypertension.